The IMPROVING CHILDREN'S COGNITIVE DEVELOPMENT THROUGH USE MEDIA BILANGA SOCKS IN GROUP B - Monalisa, Weka; Imran, Ranny Fitria; Haryono, Mimpira (Early Childhood Research and Practice, 2023)
This study draws the conclusion that through activities using number bag media can improve the cognitive development of children in PAUD AMANDA Seluma District. This increase can be seen from the increase in the percentage after the implementation of the actions in cycle I and cycle II. Implementation of the action in the first cycle, the percentage shown from the first cycle is 67%. The implementation of the actions in Cycle II showed an increase compared to the actions in Cycle I. The percentage of achievement results in Cycle II was 93% in the Very Good Developing criteria, meaning that it achieved the research success criteria of 75% - 100%.